Adverse events of common psychiatric medications: an umbrella review - Bartellas, K (2016)
BACKGROUND: Psychiatric medications were the second most prescribed therapeutic class in the United States in 2015 with 547 million prescriptions. Adverse events of medications are very common, can be distressing to patients and are often underreported in the primary studies. The purpose of this thesis is to systematically review the scientific literature to estimate the prevalence and burden of adverse events among the most common psychiatric medications. METHODS: The 23 most commonly prescribed psychiatric medications in the United States as well as eight psychiatric medications from the World Health Organization's Essential Medicine List were included. A systematic and comprehensive search was conducted to retrieve all published and unpublished systematic reviews with meta-analyses to assess adverse events of individual psychiatric medications (this process of collecting secondary publications and not primary studies is called "umbrella review"). Seven databases (Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Embase, Medline, PreMedline, PsycINFO and PubMed) were searched between 1946 and 2016. Prevalence rates and effect estimates were extracted by two independent reviewers and summarised. A quality analysis was performed on included reviews using the AMSTAR (assessing the methodological quality of systematic reviews) tool and all were rated as medium or high quality reviews. RESULTS: 69 systematic reviews and meta-analyses published were eligible for data extraction, quality appraisal and quantitative synthesis. Antipsychotic medications (60%) accounted for the majority of the findings, followed by antidepressants (16%), stimulants (13%), mood stabilisers (8%) and anxiolytics (3%). The strongest associations were between amitriptyline and sexual dysfunction (N=442, odds ratio [OR] 16.6; 95% Confidence Intervals [CI] 4.6 to 60.6), aripiprazole and somnolence (N=569, OR 25.8; 95% CI 1.3 to 112.3) and olanzapine and weight gain (N=249, OR 32.0; 95% CI 1.7 to 98.4). Overall, neurological adverse events were reported most frequently for antidepressant, antipsychotic and anxiolytic medication classes. Patient characteristics, particularly age and diagnosis, explained differences in adverse events across and within medication classes. DISCUSSION & CONCLUSION: To my knowledge, this is the first umbrella review on the tolerability profiles of 31 common psychiatric medications worldwide. Many medications were linked to adverse events through a weak or moderate strength of association and additional factors contributed to the variability in adverse outcome reporting aside from patient characteristics. Findings from this review need to be examined with the efficacy profiles of the medications and the clinical circumstances of the individual patients.